The influence of Russian traditions on the formation of Khakass farm housing in Khakass-Minusinsk region in 19th - 20th centuries - Tuguzhekova, Valentina N.; Prischepa, Evgenii V. (The New Research of Tuva, 2019)
The article deals with the problems of the development of farm housing among the indigenous inhabitants of Khakass-Minusinsk region in the 19th and 20th centuries. As a result of the development and settlement of the region, the cultural and economic relationships of the Khakass people with the Russians meant establishing contacts between different cultural traditions. This triggered the process of cultural interaction, an important place wherein belonged to the development and evolution of the main types of farm housing. It began with the transformation of traditional settlements and with the appearance of the mixed forms of farm housing where ethnically significant features underwent radical erosion, preserving only some of the traditional elements. Progressively, the Russian-type farm buildings became widespread throughout the region. As a result, the early 20th century witnessed a formation of Khakass farmhouse, which featured both winter and summer outbuildings and houses (a practice borrowed from Russians), thus enabling indigenous farmers to live on the farm permanently. In the second half of the 20th century, the design of the Khakass farm housing modeled on the Russian tradition becomes typical, with its street orientation, and the complex of living quarters and outbuildings of agricultural and cattle-breeding use.